Hohenbergia densa (Bromeliaceae), a new species from Rio Grande do Norte, Brazil - Cavalcante, Brayan Paiva; Silva, Maciel Florêncio Da (Phytotaxa, 2021)
We describe a new species from Rio Grande do Norte (Brazil), Hohenbergia densa, that inhabits the dry vegetation of the state. This new species can be recognized by its short and robust habit, differing from other Caatinga-endemic species of the region, that commonly present a broader rosette with a long inflorescence axis. Additionally, we provide illustrations, habit, phenology, a map of occurrence, and a table of morphological comparisons with similar taxa.